Use of PowerPoint presentation as a teaching tool for undergraduate students in the subject of gerodontology - Shigli, Kamal; Agrawal, Neha; Nair, Chandrasekharan; Sajjan, Suresh; Kakodkar, Pradnya; Hebbal, Mamata (The journal of Indian Prosthodontic Society, 2016)
Aim: Though different teaching learning media have been employed in the instruction of geriatric dentistry, their efficacy has not been adequately evaluated. This study was conducted with the aim to determine the efficacy of a PowerPoint presentation in teaching gerodontology. Materials and Methods: This is a prospective follow-up study using a pre- and post-intervention assessment. A pilot study was conducted on the final year students to check the feasibility of the study. A convenience sampling procedure was used. All interns (n = 80) of the Modern Dental College and Research Centre, Indore, India were invited to participate. Interns completed a 24-item questionnaire documenting their current knowledge on gerodontology. One week after a 30 min PowerPoint presentation on gerodontology, the same interns completed the same questionnaire again, providing an indication of the efficacy of the learning tool. Paired t-test and McNemar test were employed for statistical analysis. Results: A statistically significant difference was observed in pre- and post-intervention scores (P < 0.05). Conclusion: The results of this study indicated that PowerPoint presentation can be used as an effective tool for improving the knowledge regarding gerodontology.